ANALYZING USER PERCEPTIONS AND DOMINANT FACTORS OF BLOOKET-BASED GAMIFICATION IN ENGLISH LEARNING - Salainti, Engelina; Rotikan, Reymond (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2026)
The swift advancement of digital technology has brought several game-based learning (GBL) platforms into the English as a Foreign Language (EFL) classroom, with Blooket standing out as a significant instrument for enhancing student engagement. The objective of this study is to examine students' perspectives and to determine the primary elements that influence their engagement in active learning through the utilization of Blooket. Employing a descriptive quantitative methodology, data were gathered through a structured questionnaire administered to 36 students in a Pre-intermediate English setting. The descriptive statistical analysis findings show a high degree of favorable impression, with students especially liking a blended learning method that blends Blooket with traditional lectures (Mean = 3.78). The study also finds that human-centered aspects are the most important ones for engagement, such as social connection with peers and a sense of personal responsibility for learning (Mean = 3.80). Logistical considerations like room layout and infrastructure are helpful, but they are not as important as the interpersonal interactions that the gamified setting creates. The results indicate that Blooket is a useful teaching tool for improving student independence and interaction in EFL classrooms.